Migrant entrepreneurs in Germany from 2005 to 2014. Their extent, economic impact and influence in Germany’s Länder - Sachs, Andreas; Hoch, Markus; Münch, Claudia; Steidle, Hanna (Gütersloh, 2016)
"Whether a founder, owner of a small-to-medium business or self-employed as a freelance professional, people with a migrant background contribute significantly to the diversity and economic strength of Germany’s labor market and its mid-ranking businesses (Mittelstand). In 2014, the entrepreneurial activities of people with a migrant background accounted for more than two milllion people in employment across Germany. Investment in education and needs-based support and advisory services in each of the Länder could increase the contributions made by the selfemployed with a migrant background to the economy and societal integration. This is the conclusion reached by the study “Migrant Entrepreneurs in Germany from 2005 to 2014. Their Extent, Economic Impact and Influence in Germany’s Länder.”"